Immune Aspects and Myometrial Actions of Progesterone and CRH in Labor. (19th October 2011) - Vrachnis, Nikolaos; Malamas, Fotodotis M.; Sifakis, Stavros; Tsikouras, Panayiotis; Iliodromiti, Zoe
Abstract : Progesterone and corticotropin-releasing hormone (CRH) have a critical role in pregnancy and labor, as changes related to these hormones are crucial for the transition from myometrial quiescence to contractility. The mechanisms related to their effect differ between humans and other species, thus, despite extensive research, many questions remain to be answered regarding their mediation in human labor. Immune responses to progesterone and CRH are important for labor. Progesterone acts as an immunomodulator which controls many immune actions during pregnancy, and its withdrawal releases the inhibitory action on inflammatory pathways. In humans, a "functional" progesterone withdrawal occurs with onset of labor through changes in progesterone metabolism, progesterone receptors, and other molecules that either facilitate or antagonize progesterone function. Placental CRH acts on the fetal pituitary-adrenal axis to stimulate adrenal production of androgens and cortisol and also acts directly on myometrial cells via its receptors. CRH also affects inflammatory signals and vice versa. Interactions between progesterone and CRH additionally occur during labor. We describe the role of these two hormones in human myometrium and their interactions with the immune system during labor.